Decision Support System for The Selection of XYZ School Head Candidates Using Topsis Method - Putri, Anisa (PT. Technology Laboratories Indonesia (TechnoLabs), 2024)
The school principal must be an integral part of the improvement of education quality, collaborating with teachers and other school staff to foster and enhance the educational quality in the school as optimally as possible according to established standards. The decision-making process for selecting a school head at the Education Office of Serdang Bedagai Regency is relatively challenging due to various criteria that influence the decision (both subjective and objective criteria). With a Decision Support System (DSS), humans can obtain information to support decision-making. The decision support system currently being developed includes the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) methods. TOPSIS is used in ranking to determine the best school head alternative. From the research results, it can be concluded, among other things: TOPSIS methods in the built decision support system is capable of providing final results that meet the criteria for the candidates for the State High School Head. The accuracy level of the testing results is 100%.